DYNAMICS OF ?-CAROTENE AND FUCOXANTHIN IN TROPICAL MARINE NAVICULA SP. GALUR NLA CELL CULTURED UNDER ENVIRONMENTAL STRESS CONDITIONS - Telussa, Ivonne
Tropical marine diatom Navicula sp. galur NLA are able to survive in the extreme environmental conditions, e.g. living under high light exposure by regulating their ?-carotene and fucoxanthin metabolism in cells. Dynamics of ?-carotene and fucoxanthin metabolic pathway in Navicula sp. galur NLA cells cultivated in modified medium in indoors and outdoors conditions were studied to understand how Navicula sp. galur NLA cells overcome environmental stresses such as conditions at high light intensity. So far, research on tropical marine diatoms Navicula sp. galur NLA as a model organism to produce a large scale ?- carotene and fucoxanthin outdoors has yet been conducted. As an organism of microscopic photosynthesis, Navicula sp. galur NLA may grow under direct sunlight exposure in which their daily and seasonal light intensities are fluctuated that reducing biomass productivity, changing cell metabolism, and disturbing photosynthesis, with the result that changing fucoxathin and ?-carotene synthesis pathway. Hence, this research aimed to study the growth of tropical marine diatom Navicula sp. galur NLA in both indoor and outdoor conditions and to understand the dynamics of accumulation of ?-carotene and fucoxanthin.